The Role of Islamic Religious Education Teachers in Shaping Pancasila Student Profiles in Junior High Schools - Ajang Santa Setiawan; Amirudin; Yadi Fahmi Arifudin (South Sulawesi Education Development (SSED), 2025)
This study seeks to examine the role of Islamic Religious Education (PAI) teachers in shaping the Pancasila Student Profiles at SMPN Satu Atap 1 Rawamerta, Karawang Regency. A qualitative approach with an exploratory case study method was employed. Data were collected through interviews with PAI teachers, principals, and students, as well as classroom observations and documentation of learning activities. The data were analyzed using the interactive analysis model by Miles and Huberman, which involved data collection, reduction, and presentation, with validity checks through triangulation. The findings reveal that PAI teachers serve as educators, facilitators, and motivators in instilling Pancasila values, such as faith, noble character, and mutual cooperation, through discussions, extracurricular activities, and community-based projects. However, challenges such as diverse student backgrounds, low interest in character-building activities, and limited curriculum time were identified. To address these issues, technology and community involvement were utilized to support the learning process. The implications of this research highlight the need for a more adaptive approach to religious education, with a focus on enhancing the role of technology and community. Future research should expand the scope to include other schools and a broader range of student backgrounds to gain a more comprehensive understanding of the role of PAI teachers in shaping the Pancasila Student Profile.